Field trip to Bagerhat in Bangladesh - CGIAR Research Program on Climate Change, Agriculture and Food Security (2012)
The CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) South Asia office recently traveled out to Bagerhat in Bangladesh, a key site of the program, to visit farmers and see how they work in the fields. This is an important aspect of the work, that the South Asia program is conducting, interacting and following farmers to reviewe their current practices. Photo : G.Bhatta (CCAFS-SA).